Fibrothecal Tumors of the Ovary - Case Report - Lamrani, M; Lakhdar, K; Sardaoui, S; Alami, Y; Tijami, F; Hachi, H; El-Hanchi, Z; Baydada, A (Clinical Journal of Obstetrics and Gynecology, 2024)
Fibrothecal tumors of the ovary are rare neoplasms, comprising less than 4% of all ovarian tumors and primarily affecting post-menopausal women. These benign tumors arise from the stromal tissue of the ovary and may produce hormones, particularly estrogen. Their diagnosis presents considerable challenges, frequently leading to misclassification as malignant ovarian tumors or uterine myomas. This report describes the case of a 59-year-old woman who presented with abdominal distension and pelvic pain. Clinical examination revealed a large, lobulated mass and imaging studies classified the right ovarian mass as ORADS 4. An exploratory laparotomy confirmed the absence of metastasis, resulting in total hysterectomy, bilateral adnexectomy, and omentectomy. The anatomopathological analysis identified the latero-ovarian mass as a fibrothecoma. Generally, fibrothecal tumors are benign with a favorable prognosis following surgical intervention. Common symptoms include pelvic pain and abdominal distension, and diagnosis typically relies on imaging techniques such as ultrasound and CT, with definitive confirmation achieved through histopathological examination. Given their potential to mimic malignant ovarian cancer, accurate diagnosis is critical and necessitates a multidisciplinary approach.